(3TQM GdajI Hf eGdcs - (3LeGd GdOjf GHi YHO Gddg eMeO Hf YHO Gddg GdWGFi GdLjGfis; (3LeGd GdOjf CHh eMeO YHO Gddg jhSa Hf gTGes ((3CMeO Hf GHQGgje Hf efUhQ GdRQGhfi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPG TQM eNJUQ Ydi CdajI Hf eGdc egPH GdebGUO hGVM GdeSGdc s
(3BNQgG (B:s
(3bO CJjfG Ydi eG CQOfG LeYg ef GdTQM hGdEYQGH aLGA TQMkG eced GdebGUO heSgd GdeYGfi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs